The Role of Bahana Mahasiswa Press in the Field of Education and Malay Culture in Riau (1983-1998) - Sukmana, Meila Dita; Ahmal, Ahmal; Yuliantoro, Yuliantoro (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The objectives of this research are: (1) To determine the early formation of Bahana Mahasiswa student press, (2) To understand the role of Bahana Mahasiswa student press in the field of education in Riau from 1983 to 1998, (3) To comprehend the role of Bahana Mahasiswa student press in the field of Malay culture in Riau from 1983 to 1998. This research utilized a historical approach, with data collection methods including literature review, interviews, and documentation. The study was conducted at the Bahana Mahasiswa Secretariat. After gathering the data, data validation was performed through source criticism by assessing the authenticity of the obtained sources through comparing data from different sources, such as comparing interview results with written evidence. Based on the research findings, it can be concluded that: (1) Bahana Mahasiswa was established in 1982 and its development was marked by its inaugural publication in July 1983, (2) The role of Bahana Mahasiswa in the field of education is inseparable from its identity as a campus press, with published news always addressing educational issues in Riau, particularly at the University of Riau, (3) The role of Bahana Mahasiswa in the field of Malay culture is manifested through the Gumam and Kilas Balik rubrics, which contain topics related to Malay culture.